1986
DOI: 10.1121/1.393676
|View full text |Cite
|
Sign up to set email alerts
|

Models of auditory masking: A molecular psychophysical approach

Abstract: Gilkey et al. [J. Acoust. Soc. Am. 78, 1207-1219 (1985)] measured hit proportions and false alarm proportions for detecting a 500-Hz tone at each of four starting phase angles in each of 25 reproducible noise samples. In the present paper, their results are modeled by fitting the general form of the electrical analog model of Jeffress [J. Acoust. Soc. Am. 48, 480-488 (1967)] to the diotic data. The best-fitting configurations of this model do not correspond to energy detectors or to envelope detectors. A detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 31 publications
5
45
0
1
Order By: Relevance
“…3͒. The negative weights for the MD model found above and below the target frequency were consistent with weighting patterns in previous MD model results ͑Ahumada and Lovell, 1971;Ahumada et al, 1975;Gilkey and Robinson, 1986͒, but only positive weights were possible in the suboptimal weighting scheme because these weights were derived from rms metrics. Note that the weights that fit to the responses of S3 for MD with the 100-Hz bandwidth were close to those fitted to the MDS model.…”
Section: Modelssupporting
confidence: 71%
See 2 more Smart Citations
“…3͒. The negative weights for the MD model found above and below the target frequency were consistent with weighting patterns in previous MD model results ͑Ahumada and Lovell, 1971;Ahumada et al, 1975;Gilkey and Robinson, 1986͒, but only positive weights were possible in the suboptimal weighting scheme because these weights were derived from rms metrics. Note that the weights that fit to the responses of S3 for MD with the 100-Hz bandwidth were close to those fitted to the MDS model.…”
Section: Modelssupporting
confidence: 71%
“…The first two are related: single critical-band ͑CB͒ models and multiple-detector ͑MD͒ models that linearly combine outputs of multiple critical bands. To date, detection patterns estimated under diotic conditions have been best predicted by a MD model ͑Ahumada and Lovell, 1971; Ahumada et al, 1975;Gilkey and Robinson, 1986;Davidson et al, 2006͒. The MD model accounted for up to 90% of the variance in one subject's responses in Ahumada and Lovell ͑1971͒ and up to 72% of the variance in one subject's responses in Gilkey and Robinson ͑1986͒.…”
Section: A Diotic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, molecular, rather than molar, analyses were conducted on the data (Green, 1964) in order to gain insight into the decision process, rather than obtaining molar measures such as loudness or accuracy. Molecular, or perceptual weight, analyses have been used for several decades (Ahumada & Lovell, 1971;Berg, 1989;de Boer & Kuyper, 1968;Gilkey & Robinson, 1986) and have found increasing application in several domains (e.g., Ahumada, 2002;Berg, 2004;Neri, Parker, & Blakemore, 1999;Oberfeld, 2009;Yu & Young, 2000). We applied this technique to a loudness judgment task, in order to estimate the influence of the sound pressure level of different temporal portions of the stimulus on global loudness.…”
Section: Experiments 1: Effects Of a Fade-inmentioning
confidence: 99%
“…In order to test model predictions and compare the effectiveness of different cues, it is useful to consider detection performance on a waveformby-waveform basis (molecular-level) for each listener (e.g., Sch€ onfelder and Wichmann, 2013). Gilkey et al (1985) and Gilkey and Robinson (1986) found that averaging detection performance across masker waveforms obscures the differences across individual waveforms and listeners, suggesting the utility of a more molecular-level approach. However, molecular-level predictions are difficult to obtain because of the unknown internal noise for each listener and the possible use of different cues by different listeners.…”
Section: Introductionmentioning
confidence: 99%